Practical Java Programming with ChatGPT - Bluck, Alan S (Orange Education Pvt Ltd, 2023)
How to use ChatGPT to write fast validated Java codeDESCRIPTIONEmbark on a Fascinating Journey into AI-Powered Software Development with ChatGPT. This transformative book challenges the conventional speed of software development by showcasing a diverse array of inquiries directed at cutting-edge AI tools, including Ask AI, ChatGPT 3.5, Perplexity AI, Microsoft Bing Chatbot based on ChatGPT 4.0, and the Phed mobile app. Diving deep into the integration of Java and ChatGPT, this book provides readers with a comprehensive understanding of their synergy in programming. Each carefully crafted question serves as a testament to ChatGPT's exceptional ability to swiftly generate Java programs. The resulting code undergoes rigorous validation using the latest open-source Eclipse IDE and the Java language, empowering readers to craft efficient code in a fraction of the usual time. The journey doesn't end there—this book looks ahead to the promising future of ChatGPT, unveiling exciting potential enhancements planned by OpenAI. These innovations are poised to usher in even more formidable AI-driven capabilities for software development.TABLE OF CONTENTS 1. Getting Started with ChatGPT2. Java Programming – Best Practices as Stated by ChatGPT3. Developing Java Code for Utilizing the ChatGPT API4. Java Program for Using Binary Search5. Installation of the Latest Open-source Eclipse Java IDE6. ChatGPT Generated Java Code for Fourier Analysis7. ChatGPT Generated Java Code for the Fast Fourier Transform8. ChatGPT Generated Java Code for Indexing a Document9. ChatGPT-Generated Java Code for Saltikov Particle Distribution10. ChatGPT-Generated Java Code to Invert a Triangular Matrix11. ChatGPT Generated Java Code to Store a Document in the IBM FileNet System12. Conclusions and the Future of ChatGPT for Program Development13. Appendices for Additional QuestionsIndex